Immunophenotypic profiles of monocytic microparticles derived from human blood monocytes and their potential role in coagulation and endothelial cell activation - Noor, Nur Azira Mohd (2020)
Monocytic microparticles (mMP) are small heterogeneous microvesicles derived from monocytes following cellular activation or apoptosis. Significant elevation of circulating mMP in various diseases increases its potential as a biomarker. However, the phenotypic and functional role of mMP derived from human blood monocytes is unknown. This study intended to characterise mMP derived from whole monocytes, CD14+ monocytes, and CD16+ monocytes by assessing surface antigen expressions and identify their role in coagulation and endothelial cell function. All monocyte subtypes were cultured in the presence of lipopolysaccharides (LPS) for 18 hours. Monocytic MP were purified from culture supernatants by ultracentrifugation before being analysed using flow cytometry. Meanwhile, prothrombin time (PT) assay was performed to assess the coagulation potential of mMP. To assess the role mMP in endothelial cells function, mMP were co-cultured with human umbilical vein endothelial cells (HUVEC). The expression level of ICAM-1 and VCAM-1 on HUVEC as well as the release of endothelial MP (eMP) upon mMP-HUVEC coculture were then determined by using real time PCR and flow cytometry respectively. This study has shown that CD14 and CD16 were expressed on all monocyte subtypesderived mMP similar to their origin cells. Additionally, CD142 were expressed on mMP and coagulation time was shortened in the presence of LPS-stimulated whole monocyte-derived mMP. Meanwhile, the expression of intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) were increased in the presence of mMP derived from whole monocytes and mMP increased the level of endothelial microparticles (eMP). These findings suggest that Annexin-V in combination with CD14 and CD16 could be possible surface markers for mMP phenotyping. Furthermore, mMP may possess procoagulant properties as CD142 on their surface may be the major player in coagulation and they were able to activate endothelial cells, suggesting a potential role in endothelial cell function.